Institutional quality and financial development: The United States perspective - Khan, Muhammad Asif; Khan, Muhammad Atif; Abdulahi, Mohamued Elyas; Liaqat, Idrees; Shah, Sayyed Sadaqat Hussain (Journal of multinational financial management, 2019)
This paper revisits the ambiguous natural resource rent and finance nexus in the context of the United States, incorporating the vital role of institutional quality in this paradigm. The literature on the subject matter lacks consensus and overlooks the institutional framework. The study utilizes a unique data set by the International Monetary Fund (IMF), considered the most comprehensive measure of financial development. Our findings based on a robust cointegration approach conclusively confirm that institutional quality is a significant prerequisite to financial development in the United States. The natural resource rent affects financial development negatively when we include proper controls in the estimation. However, we find that institutional quality moderates the natural resource rent and finance nexus. We recommend that policymakers and researchers consider the importance of institutions to come up with realistic estimations and policy inputs.